Vibration isolation analysis of new design OEM damper for malaysia vehicle suspension system featuring MR fluid - Unuh., M. H.; Muhamad, Pauziah; Mohd Yatim, Norfazrina Hayati; Ismail, Mohamad Amiruddin (Institute of Physics Publishing, 2018)
The applications of semi-active damper employing magnetorheological (MR) fluids keep increasing in fulfilling the demand to control undesired vibration effect. The aim of this study is to introduce the new design of damper for Malaysian vehicle model as well to evaluate its effectiveness in promoting comfort. The vibration isolation performance of the OEM damper featuring MR fluid was analysed physically under real road profile excitation experimentally. An experiment using quarter car rig suspension and LMS SCADAS Mobile was conducted to demonstrate the influence of current in controlling the characteristics of MR fluid in alter the damping behaviour under 5 cm bump impact. Subsequently, the displacement values were measured with respect to time. The new design OEM damper featuring MR fluid was validated by comparing the data with original equipment manufacturer (OEM) passive damper results under the same approach of testing. Comparison of numerical data of the new design OEM damper shown that it can reduce the excitation amplitude up to 40% compared to those obtained by OEM passive damper. Finally, the new design OEM damper featuring MR fluid has effectively isolated the disturbance from the road profile and control the output force.